Telehealth Physical Therapy: More Than an Alternative to In Person Care of the Young Athlete - Joseph T. Molony Jr. (International Journal of Sports Physical Therapy)
The shift to telehealth due to COVID-19 revealed that a new care model for the young athlete, which combines in-person and virtual visits, could be an enhancement to in-person care alone. This clinical suggestion is novel as it discusses the utility of a hybrid care model for the young athlete, which has not yet been described. Interacting with the patient and family virtually in the home environment offers benefits that are difficult to achieve in the clinic. Opportunities such as the ability to custom tailor the home program with consideration of the patient’s learning abilities, provide movement quality feedback outside of the clinical environment, observe parent/caregiver feedback, involve family members who may not be available to attend in-person visits, and the possibility of converting an in-person cancelation to a telehealth visit in order to maintain continuity of care, are examples of how this model may optimize treatment. Consideration of investigating the impact on clinical outcomes and cost effectiveness is recommended.